Population Genomics of a Cosmopolitan Weed Provides Insights Into Its Local Adaptation and Recent Demographic History - Marilia Souza Lucas; Christoph Rosche; Isabell Hensen; Stefan G. Michalski; Dávid U. Nagy; Diana Gamba; Renske E. Onstein; Karime Abidkulova; Mohammad Al‐Gharaibeh; Ali A. Al‐Namazi; Sirwan Babaei; Fernando Bastida; et al. (Molecular Ecology, 2026)
Invasive plant species present a growing ecological and economic challenge, and often adapt rapidly to their novel environments through complex demographic and evolutionary processes. Invasion genomics offers powerful tools to disentangle these processes, but most studies rely on geographically narrow sampling across native and non‐native ranges. Erigeron canadensis is a cosmopolitan weed native to North America that has successfully invaded diverse climates worldwide. We used double‐digest restriction site‐associated DNA sequencing (ddRADseq) to investigate the genetic diversity and structure of 280 E. canadensis populations across the Northern Hemisphere. We found that native and non‐native populations maintained comparable genetic diversity. Population structure analyses revealed four genetic clusters that were mainly differentiated along latitudinal and aridity gradients. However, one cluster was strongly overrepresented in the non‐native compared to the native range. In the native range, genetic differentiation was shaped by spatial and environmental gradients, while in non‐native regions human‐mediated dispersal and repeated introductions disrupted environmentally driven genetic structure. Migration network analyses revealed limited intercontinental connectivity and a possible role of long‐distance dispersal in within‐range expansions. Genomic offset analyses showed that genotype‐environment mismatches in non‐native populations associated with reduced growth and reproduction. Together, our results indicate that the invasion dynamics of E. canadensis were driven by multiple introductions, population admixture, and lineage sorting, while some genotypes contributed disproportionately to the spread of this invader. The presence of apparent maladaptation suggests that even long‐established invaders may still be evolving in response to their novel environment, raising concerns about potential future expansions.

Extreme capital breeding for giants: Effects of body size on humpback whale energy expenditure and fasting endurance - Fredrik Christiansen; Peter T Madsen; Virginia Andrews-Goff; Mike C Double; Jason R How; Phil Clapham; Yulia Ivashchenko; Dmitry Tormosov; Kate R Sprogis (Ecological Modelling, 2025)

Dmitry Tormosov 1937–2024 - Phillip J. Clapham; Vladimir N. Burkanov; Yulia V. Ivashchenko; Robert L. Brownell (Marine Mammal Science, 2025)

Anthropogenic scarring of western gray whales ( Eschrichtius robustus ) - Amanda L. Bradford; David W. Weller; Yulia V. Ivashchenko; Alexander M. Burdin; Robert L. Brownell, Jr (Marine Mammal Science, 2009)
Western gray whales ( Eschrichtius robustus ) are critically endangered and anthropogenic threats, such as entanglement in fishing gear and collisions with vessels, may be acting to limit recovery of the population. Thus, examining the magnitude of such anthropogenic interactions using a scar‐based approach is warranted. A multi‐year (1995–2005) photo‐identification study of western gray whales on their feeding ground off northeastern Sakhalin Island, Russia, has resulted in a large data set of digital and film images of 150 individuals. These images were reviewed and scored for anthropogenic scarring by recording the presence of visible scars resulting from fishing gear entanglement and vessel collisions in 21 defined body regions. In total, 20.0% ( n = 30) of whales identified during the study period had detectable anthropogenic scarring, with 18.7% ( n = 28) determined to have been previously entangled in fishing gear at least once and 2.0% ( n = 3) to have survived at least one vessel collision. These estimates are likely to be conservative given the nature of the photo‐identification data set, but indicate that male and female western gray whales are subject to anthropogenic interactions. Future studies designed to systematically estimate the frequency and rates of anthropogenic events are needed and would have direct conservation and management implications.